2016
DOI: 10.1002/spe.2421
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of dependency analysis in static architecture compliance checking

Abstract: SUMMARYArchitecture compliance checking (ACC) is an approach to verify conformance of implemented program code to high-level models of architectural design. Static ACC focuses on the modular software architecture and on the existence of rule violating dependencies between modules. Accurate tool support is essential for effective and efficient ACC. This paper presents a study on the accuracy of ACC tools regarding dependency analysis and violation reporting. Ten tools were tested and compared by means of a cust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 49 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…It provides developers with inconsistency awareness as they are developing through margin alerts, through auto-complete alerts and through the architectural model itself, also integrating a facility where developers can email architects with alerts when inconsistencies are introduced. In addition, a recent study by Pruijt et al (2016) has shown that JITTAC was more holistic and effective, in terms of detecting all the source code dependencies in software systems than the other academic and commercial offerings in the area.…”
Section: Existing Approachesmentioning
confidence: 99%
“…It provides developers with inconsistency awareness as they are developing through margin alerts, through auto-complete alerts and through the architectural model itself, also integrating a facility where developers can email architects with alerts when inconsistencies are introduced. In addition, a recent study by Pruijt et al (2016) has shown that JITTAC was more holistic and effective, in terms of detecting all the source code dependencies in software systems than the other academic and commercial offerings in the area.…”
Section: Existing Approachesmentioning
confidence: 99%
“…By use we mean any time a declares a variable of type b, invokes a method on an object of type b, accesses a field of an object of type b, or inherits from type b. The way we calculate dependencies complies with the benchmark and guidelines provided by Pruijt et al [45].…”
Section: Calculating Extentmentioning
confidence: 99%
“…We rely on the notion of compliance [52] between MyA and MyRA, which we implemented as virtual conformance. The conformance relationship in MDE defines a typing relationship between objects and their types.…”
Section: Model Promotion Transformationmentioning
confidence: 99%